2017
DOI: 10.1080/17535069.2017.1312509
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and social cohesion: the case of Jane-Finch, a highly diverse lower-income Toronto neighbourhood

Abstract: Diversity has increasingly emerged as the core focus of many studies concerning factors impacting on social cohesion. Various scholars have concluded that diversity is detrimental to cohesion. Most of this research, however, draws generalisations based upon quantitative data and fails to account for the impact of inequality, segregation and discrimination, and their interconnectedness to diversity. This research provides an indepth qualitative analysis of the perceptions of inhabitants of a diverse Toronto nei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 59 publications
(68 reference statements)
0
10
0
Order By: Relevance
“…Social cohesion in the literature is defined in general terms and often used interchangebly with social capital (Letki, 2008;Putnam, 2007). More detailed elaborations of the concept refer to social contacts, networks, social order, shared values and norms, place attachment and shared identity (Ahmadi, 2018;Forrest & Kearns, 2001;Tasan-Kok et al, 2014). A rigorous study of the phenomenon requires careful operationalization to guide robust empirical research.…”
Section: Neighbourhood Cohesionmentioning
confidence: 99%
See 3 more Smart Citations
“…Social cohesion in the literature is defined in general terms and often used interchangebly with social capital (Letki, 2008;Putnam, 2007). More detailed elaborations of the concept refer to social contacts, networks, social order, shared values and norms, place attachment and shared identity (Ahmadi, 2018;Forrest & Kearns, 2001;Tasan-Kok et al, 2014). A rigorous study of the phenomenon requires careful operationalization to guide robust empirical research.…”
Section: Neighbourhood Cohesionmentioning
confidence: 99%
“…Social cohesion, in turn, involves notions of belonging and spatial mobility (commuting and residential turnover), affirming that "the building blocks of social cohesion reside within places" (Kearns & Forrest, 2000, p.1001. A recent literature review on social cohesion identified three widely shared perspectives: a) common values and norms, b) the existence of social ties and networks and c) neighbourhood attachment (Ahmadi, 2018). Previous scholarship has placed a lot of emphasis on these qualifiers and has explored their significance on social cohesion mostly through qualitative research and compelling narratives on building social networks, solidarity and cultural diversity (Altman & Low, 1992;Forrest & Kearns, 2001).…”
Section: Neighbourhood Cohesionmentioning
confidence: 99%
See 2 more Smart Citations
“…Toronto is also host to more than one-third of the Canadian newcomer population. As evidenced in the recent work of Ahmadi (2017Ahmadi ( , 2018, the rhetoric of a multicultural and diverse Toronto has continued to serve political parties in power whilst also limit the authentic impact (especially as realized through economic redistribution, social justice, and anti-racism) on marginalized communities. The emergence of St. James Town and Regent Park, as one such material illustration, occurred in reaction to (i) the federal/provincial government desire to (appear to) prioritize public housing; and (ii) the de-racialization of Canadian immigration policy (Boudreau et al 2009).…”
Section: Spatial and Political Contextmentioning
confidence: 99%